The re-expression of Collagen Type II, Aggrecan and Sox 9 in Tissue-Engineered Human Articular Cartilage - Sha'ban, Munirah; Saim, Aminuddin; Casim, Samsudin Osman; Kienhui, Chua; Nor Hussien, Fuzina; Idrus, Ruszymah (John Wiley & Sons, Ltd., 2005)
This study was designed to verify the optimal· basic culture media that promote chondrocytes proliferation in vitro in order to facilitate adequate amount of chondrocytes for cartilage reconstructionas well as maintaining cartilage specific phenotype. Human articular chondrocytes were cultured in three types of basic culture media Ham's F12, DMEM and the equivalent mixture of F12:DMEM. Cultured chondrocytes were trypsinized as they reached confluency. The viability and total number of cell were recorded at every passage. Large-scale culture expansion was used to reconstruct tissue-engineered cartilage. Quantitative RT-PCR analysis was used to evaluate the expression of collagen Type II, collagen Type I, aggrecan and Sox 9 gene, both in monolayer culture and in the engineered cartilage. The mixture of F12:DMEM promotes significantly greater (p<0.05) chondrocytes proliferation at every passage compared to the individual medium. Monolayer cultured chondrocytes exhibited down-regulation expression pattern of collagen Type II gene, aggrecan and Sox 9, whilst the expression of collagen Type I is up-regulated. Tissue-engineered cartilage morphologically and histologically resembled normal hyaline cartilage. Moreover, tissue-engineered cartilage re-expressed the specific chondrogenesis markers; collagen Type II, aggrecan and Sox 9. In conclusion, the mixture of F12:DMEM enhanced human articular chondrocytes proliferation thus provided adequate amount of chondrocytes for cartilage reconstruction. The new cartilage formed phenotypically resembles native cartilage. This results hold promise for the use of tissue-engineered cartilage implant for future orthopaedic reconstructive surgery